2015
DOI: 10.1109/map.2015.2414492
|View full text |Cite
|
Sign up to set email alerts
|

SAR imaging-based techniques for Low Permittivity Lossless Dielectric Bodies Characterization

Abstract: The following contribution aims to test two synthetic aperture radar (SAR)-image-based techniques to obtain geometry and constitutive parameter information about low-permittivity lossless dielectric materials. While characterization of high-permittivity dielectrics is relatively affordable in SAR images, the low amount of power reflected back by lowpermittivity bodies makes their characterization a challenging task. The first proposed technique combines two illumination angles (normal and 45 ) to overcome the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Near field mm-wave imaging systems are the primary means of detecting concealed metallic weapons such as handguns [19]. Various studies have shown that synthetic aperture radar (SAR) images can be used for accurate identification and characterization of weak dielectric objects on the body surface [20][21][22]. Recent studies have discussed the feasibility of weak dielectric characterization using a focused continuous wave radar scanning system by developing a ray-based virtual source model [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Near field mm-wave imaging systems are the primary means of detecting concealed metallic weapons such as handguns [19]. Various studies have shown that synthetic aperture radar (SAR) images can be used for accurate identification and characterization of weak dielectric objects on the body surface [20][21][22]. Recent studies have discussed the feasibility of weak dielectric characterization using a focused continuous wave radar scanning system by developing a ray-based virtual source model [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Yurduseven et al proposed a fast simulation of full-size frequency-diverse aperture for imaging of humanscale targets [16]. Alvarez et al demonstrated the feasibility of synthetic aperture radar screening to estimate the geometry and constitutive parameter information for low-permittivity lossless dielectric objects attached to flat and curved metallic plates [19][20][21]. Focused-beam continuous-wave radar was used for object characterization in security applications [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Our study focuses on determining the same properties of the potential threats automatically and by using wideband radar images with high range resolution. In [29,36], it has been shown that synthetic aperture radar (SAR) imaging can be used for deriving such characteristics for low-permittivity and lossless foreign objects. We apply the same method to our wideband radar images.…”
Section: Thesis Motivationmentioning
confidence: 99%